Plano de la ciudad de Iquitos - (:unkn) unknown (My University, 1999)
Map of the city of Iquitos, made by the IIAP and the center of geographic information of the Peruvian Amazon, it shows the southern and northern boundary of the city of Iquitos.

Plano de la ciudad de Iquitos, realizado por el IIAP y el centro de información geografica de la amazonia peruana, en ella se muestra el limite zona sur y norte de la ciudad de Iquitos
Map of the city of Iquitos
Keywords: Incluye: Plano de la ciudad de Iquitos; Rio Itaya; Rio Amazonas; Rio Nanay; Lago Moronacocha; Punchana; Belén; Maynas; San Juan; Río Itaya; Lago Moronacocha; Río Amazonas.; Iquitos (Peru)--maps; Peru--cartographic materials; Peru--maps